EFFICACY OF INTRAVENOUS TIROFIBAN THERAPY IN LACUNAR STROKE PATIENTS - Ahmet Yabalak; Petek Sarli; Murat Yilmaz; Hilmiye Tokmak; Muhammed Nur Ogun (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Background: Lacunar ischemic infarcts are small-sized infarcts that develop as a result of occlusion of perforating arteries. Although its pathophysiology differs from other stroke types, there is no separate treatment option from non-cardioembolic strokes. Early neurological worsening in lacunar strokes is a common condition reported up to 41%. There is no effective treatment method to prevent or correct progression. Tirofiban is a reversible receptor antagonist of glycoprotein IIb/IIIa. There are cohort studies with small number of cases related to its use in ischemic stroke. We wanted to evaluate its effectiveness on the progression of lacunar stroke because it is a powerful antiplatelet agent. Objective: Tirofiban is a reversible receptor antagonist of glycoprotein IIb/IIIa. There are cohort studies with small number of cases related to its use in ischemic stroke. We wanted to evaluate its effectiveness on the progression of lacunar stroke because it is a powerful antiplatelet agent. Methods: The data of patients who were followed up in our clinic with the diagnosis of lacunar stroke between August 2020 and May 2022 and who received tirofiban treatment were evaluated retrospectively. Patients' ages, infarct localizations, NIHSS scores at admission, at the beginning and end of tirofiban treatment, and 3rd month mRS scores were recorded. Results: Fifteen patients, 11 male and 4 female, were included in the study. The mean age of the patients was 68.73±9.58 (range, 51-85). Tirofiban was started proactively in 2 patients, after progression in 13 patients. The NIHSS scores were 7.20±2.65 at the start of the infusion, and 4.80±3.93 after the infusion, and the decrease was statistically significant (P=0.010). Conclusion: These findings suggest that intravenous tirofiban therapy is a safe and effective treatment option to stop symptomatic fluctuations and shorten the duration of deficit in patients with progressive lacunar stroke.